Larga noche hacia mi madre: Foucault, madness and memory as an lost aftertaste - Alvarado Vega, Óscar Gerardo (2022)
In this approach to a Costa Rican novel, we resort to the Foucauldian concept of madness as a theoretical starting point. The analyzed text presents the manifestation of madness as a space of physical and mental alienation that overwhelms Tito's mother. Faced with the desperation that it provokes in him, the delirium ends up making a dent in him, too, and both are immersed in that world of darkness prefigured from the title itself. In such a way, the night is the advent of a social and mental madness, which is precisely the conclusion of our analysis. This because madness is also a social and historical construct to alienate the subject from the power of discourse.